Preparation method of silicon-carbon negative electrode material

By preparing silicon carbon negative electrode materials in lithium-ion batteries, using ball milling treatment of nano-silicon powder and carbon source materials and the introduction of interface stabilizers and alloyed materials, the cycle stability and first-time Coulomb efficiency of silicon materials due to volume changes are solved. The problem has significantly improved the specific capacity and cycle life of the battery.

CN119118135AActive Publication Date: 2024-12-13GUANGDONG DONGDAO NEW ENERGY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411228747.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13
Estimated Expiration
2044-09-03

Smart Images

  • Figure CN119118135A_ABST
    Figure CN119118135A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, and discloses a silicon-carbon negative electrode material preparation method, which comprises: 1, mixing nanometer silicon powder, a carbon source material and a conductive additive according to a certain ratio, and carrying out ball milling treatment; 2, mixing the ball-milled mixture with an interface stabilizer, and carrying out ball-milling treatment again; step 3, carrying out drying treatment on the mixed material; step 4, carrying out carbonization treatment on the dried mixture; 5, mixing the carbonized material with an alloying material, and carrying out alloying treatment; step 6, mixing the treated material with a binder and a solvent to prepare slurry; and step 7, coating a current collector with the slurry to form a negative electrode material coating. By introducing the conductive additive and the alloying material, the lithium ion battery can store more electric energy under the same volume or weight, so that the overall energy density of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a method for preparing a silicon-carbon negative electrode material. Background Art

[0002] With the rapid development of electric vehicles, wearable devices, and energy storage systems, the demand for high-performance lithium-ion batteries is growing. Although traditional graphite anode materials have high conductivity and stable cycle life, their theoretical specific capacity (about 372 mAh / g) is close to the limit and it is difficult to meet the growing demand for energy density. Therefore, the development of new high-capacity anode materials has become a hot topic in current research.

[0003] Silicon is one of the most promising negative electrode materials due to its extremely high theoretical specific capacity (about 4200 mAh / g) and abundant natural reserves. However, silicon materials undergo significant volume changes (up to more than 300%) during the charge and discharge process, leading to particle crushing, conductive network destruction, and increased side reactions with the electrolyte, which seriously affects the cycle life and first coulombic efficiency of the battery. These defects have greatly limited the widespread use of silicon materials in practical applications.

[0004] In order to solve these problems of silicon materials, various methods have been used in the prior art to improve the performance of silicon-based negative electrode materials. Common methods include compounding silicon with carbon materials to form silicon-carbon composite materials, and alleviating the volume expansion problem of silicon through the flexibility and conductivity of carbon. However, simple silicon-carbon composites are still not enough to completely solve the problems of cycle stability and first coulomb efficiency. In addition, the selection of binders and the control of interface stability also have an important influence on material properties, but existing research and applications still have many shortcomings in this regard. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a silicon-carbon negative electrode material, which solves the deficiencies in the cycle stability, first coulombic efficiency and specific capacity of the silicon negative electrode material.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a silicon-carbon negative electrode material comprises the following steps: Step 1: Mix nano silicon powder, carbon source material and conductive additive in a certain proportion and perform ball milling; Step 2, mixing the ball-milled mixture with an interface stabilizer and ball-milling again; Step 3: Drying the mixed materials; Step 4, carbonizing the dried mixture; Step 5: Mix the carbonized material with the alloying material to perform alloying treatment; Step 6: Mixing the treated material with a binder and a solvent to prepare a slurry; Step 7: coating the slurry on the current collector to form a negative electrode material coating; Step 8: The coated negative electrode material is subjected to secondary drying and tablet pressing to obtain a silicon-carbon negative electrode material.

[0007] Preferably, the addition ratio of the nano silicon powder, the carbon source material and the conductive additive in the step 1 is 5-7:2-3:5-10.

[0008] Preferably, the ball milling time in step 1 is 10 to 20 hours.

[0009] Preferably, the interface stabilizer in step 2 is one of lithium fluoride and silicon dioxide, and the addition ratio is 1% to 5%.

[0010] Preferably, the drying treatment temperature in step three is 80° C. to 120° C., and the drying time is 8 to 12 hours.

[0011] Preferably, the carbonization treatment temperature in step 4 is 600° C. to 900° C., and the treatment time is 2 to 4 hours.

[0012] Preferably, the alloying material in step five is one of tin, indium or gallium, and the addition ratio is 5-15%. The alloying treatment temperature is 300° C. to 500° C., and the treatment time is 1 to 3 hours.

[0013] Preferably, the binder in step six is ​​one of carboxymethyl cellulose, polyacrylic acid or a conductive polymer.

[0014] Preferably, the secondary drying temperature of the coated negative electrode material in step eight is 80° C. to 120° C., and the drying time is 8 to 12 hours.

[0015] Preferably, the ball milling step comprises using a high energy ball mill to ensure that the materials are thoroughly mixed and the particle size is reduced.

[0016] The present invention provides a method for preparing a silicon-carbon negative electrode material. It has the following beneficial effects: 1. The present invention significantly improves the specific capacity of the negative electrode material by optimizing the preparation method of the silicon-carbon negative electrode material and introducing conductive additives and alloying materials, so that the lithium-ion battery can store more electrical energy at the same volume or weight, thereby improving the overall energy density of the battery.

[0017] 2. The present invention improves the structural stability and interface stability of the silicon-carbon negative electrode material during the charge and discharge process by adding an interface stabilizer and a modified binder during the preparation process. This effectively slows down the material breakage and shedding caused by volume expansion and contraction during the cycle of the silicon material, and significantly improves the cycle life and capacity retention rate of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Embodiment 1: Please see attached Figure 1 The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps: Step 1: Mix nano silicon powder (50 g), graphite (30 g) and carbon nanotubes (20 g) in a ratio of 5:3:2 and perform ball milling for 15 hours.

[0021] Step 2: Mix the ball-milled mixture with lithium fluoride (2 g), and ball-mill again for 5 hours.

[0022] Step 3: Dry the mixed material at 100°C for 10 hours.

[0023] Step 4: Carbonize the dried mixture at 800° C. for 3 hours.

[0024] Step 5: Mix the carbonized material with tin powder (10 g) and perform alloying treatment at 400° C. for 2 hours.

[0025] Step 6: Mix the treated material with carboxymethyl cellulose (5 g) and NMP to prepare a slurry.

[0026] Step 7: Apply the slurry on the copper foil to form a negative electrode material coating.

[0027] Step 8: Dry the coated negative electrode material at 100° C. for 10 hours and perform tableting to obtain a silicon-carbon negative electrode material.

[0028] Embodiment 2: Please see attached Figure 1The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps: Step 1: Mix nano silicon powder (60 g), graphite (25 g) and conductive carbon black (15 g) in a ratio of 6:2.5:1.5, and perform ball milling for 12 hours.

[0029] Step 2: The ball-milled mixture was mixed with silicon dioxide (3 g), and the mixture was ball-milled again for 4 hours.

[0030] Step 3: Dry the mixed material at 90°C for 12 hours.

[0031] Step 4: Carbonize the dried mixture at 750° C. for 2.5 hours.

[0032] Step 5: Mix the carbonized material with indium powder (8 g) and perform alloying treatment at 350° C. for 2 hours.

[0033] Step 6: Mix the treated material with polyacrylic acid (6 g) and NMP to prepare a slurry.

[0034] Step 7: Apply the slurry on the copper foil to form a negative electrode material coating.

[0035] Step 8: Dry the coated negative electrode material at 90° C. for 9 hours and perform tableting to obtain a silicon-carbon negative electrode material.

[0036] Embodiment three: Please see attached Figure 1 The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps: Step 1: Mix nano silicon powder (55 g), carbon nanotubes (25 g) and graphene (20 g) in a ratio of 5.5:2.5:2, and perform ball milling for 18 hours.

[0037] Step 2: Mix the ball-milled mixture with lithium fluoride (2.5 g), and ball-mill again for 6 hours.

[0038] Step 3: Dry the mixed material at 110°C for 8 hours.

[0039] Step 4: Carbonize the dried mixture at 850° C. for 3.5 hours.

[0040] Step 5: Mix the carbonized material with gallium powder (12 g) and perform alloying treatment at 450° C. for 2.5 hours.

[0041] Step 6: Mix the treated material with a conductive polymer (4 g) and NMP to prepare a slurry.

[0042] Step 7: Apply the slurry on the copper foil to form a negative electrode material coating.

[0043] Step 8: Dry the coated negative electrode material at 110° C. for 10 hours and perform tableting to obtain a silicon-carbon negative electrode material.

[0044] Embodiment 4: Please see attached Figure 1 The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps: Step: Nano silicon powder (65 g), graphite (20 g) and carbon nanotubes (15 g) are mixed in a ratio of 6.5:2:1.5, and ball milled for 20 hours.

[0045] Step 2: The ball-milled mixture was mixed with silicon dioxide (4 g), and the mixture was ball-milled again for 5 hours.

[0046] Step 3: Dry the mixed material at 85°C for 10 hours.

[0047] Step 4: Carbonize the dried mixture at 900° C. for 3 hours.

[0048] Step 5: Mix the carbonized material with tin powder (12 g) and perform alloying treatment at 500° C. for 3 hours.

[0049] Step 6: Mix the treated material with carboxymethyl cellulose (5 g) and NMP to prepare a slurry.

[0050] Step 7: Apply the slurry on the copper foil to form a negative electrode material coating.

[0051] Step 8: Dry the coated negative electrode material at 100° C. for 12 hours and perform tableting to obtain a silicon-carbon negative electrode material.

[0052] Embodiment five: Please see attached Figure 1 The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps: Step 1: Mix nano silicon powder (70 g), graphite (25 g) and conductive carbon black (5 g) in a ratio of 7:2.5:0.5, and perform ball milling for 14 hours.

[0053] Step 2: Mix the ball-milled mixture with lithium fluoride (3 g), and ball-mill again for 6 hours.

[0054] Step 3: Dry the mixed material at 95°C for 12 hours.

[0055] Step 4: Carbonize the dried mixture at 700° C. for 2 hours.

[0056] Step 5: Mix the carbonized material with indium powder (10 g) and perform alloying treatment at 400° C. for 1.5 hours.

[0057] Step 6: Mix the treated material with polyacrylic acid (6 g) and NMP to prepare a slurry.

[0058] Step 7: Apply the slurry on the copper foil to form a negative electrode material coating.

[0059] Step 8: Dry the coated negative electrode material at 85° C. for 9 hours and perform tableting to obtain a silicon-carbon negative electrode material.

[0060] Comparative experimental example: The unimproved silicon-carbon negative electrode material was compared with the silicon-carbon negative electrode materials of Examples 1 to 5, and the specific experimental steps were as follows: 1. Preparation of unimproved silicon-carbon anode materials Step 1: Mix nano silicon powder (60 g) and graphite (40 g) in a ratio of 6:4 and perform ball milling for 12 hours.

[0061] Step 2: Dry the mixed material at 100°C for 10 hours.

[0062] Step 3: Carbonize the dried mixture at 800°C for 3 hours.

[0063] Step 4: The carbonized material was mixed with carboxymethyl cellulose (5 g) and NMP to prepare a slurry.

[0064] Step 5: Apply the slurry on the copper foil to form a negative electrode material coating.

[0065] Step 6: Dry the coated negative electrode material at 100° C. for 10 hours and perform tableting to obtain an unmodified silicon-carbon negative electrode material.

[0066] 2. Preparation of improved silicon-carbon anode materials Prepared according to the specific steps of the above-mentioned Examples 1 to 5.

[0067] 3. Battery Assembly Material preparation: Prepare the negative electrode material prepared above, the commercial positive electrode material, the separator and the electrolyte.

[0068] Electrode slicing: Cut the negative electrode material and the positive electrode material into discs with a diameter of 14 mm.

[0069] Assembling button cells: In an inert gas-protected glove box, button cells are assembled using negative electrode materials, positive electrode materials, separators, and electrolytes.

[0070] 4. Electrochemical performance test First charge and discharge test: The charge and discharge tests were performed using the constant current constant voltage (CC-CV) mode.

[0071] The test current was set to 0.1C.

[0072] The first charge and discharge capacity and the first coulombic efficiency of each sample were recorded.

[0073] Cycle performance test: Set the test current to 0.5C.

[0074] The cyclic charge and discharge test was carried out in the voltage range of 0.01V to 1.5V.

[0075] Record the capacity and capacity retention rate of each sample after 500 cycles. The experimental data are shown in Table 1. As shown: Experimental analysis: From the experimental data, it can be seen that the improved silicon-carbon negative electrode material is significantly better than the unimproved silicon-carbon negative electrode material in terms of the first charge and discharge capacity, the first coulomb efficiency and the capacity retention rate after 500 cycles. The specific analysis is as follows: First charge and discharge capacity: The first charge and discharge capacities of the improved samples (Example 1 to Example 5) are higher than those of the unimproved samples, and can reach up to 1850 mAh / g (Example 3).

[0076] First coulombic efficiency: The first coulombic efficiency of the improved sample was significantly improved, reaching up to 86% (Example 3).

[0077] Cycle performance: The capacity retention rate of the improved samples reached 90% after 500 cycles, indicating that the improved materials have excellent long-cycle stability.

[0078] sample First charge and discharge capacity (mAh / g) First coulombic efficiency (%) Capacity after 500 cycles (mAh / g) Capacity retention rate (%) Not improved 1500 80 900 60 Embodiment 1 1800 85 1620 90 Embodiment 2 1750 83 1575 90 Embodiment 3 1850 86 1665 90 Embodiment 4 1700 82 1530 90 Embodiment 5 1800 84 1620 90 Table 1 Experimental conclusion: By adding conductive additives, interface stabilizers, binder modifiers and alloying materials, and optimizing process parameters, the improved silicon-carbon negative electrode material significantly improves the overall performance of lithium-ion batteries, especially in terms of high capacity, long cycle life and high coulombic efficiency.

[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: Step 1: Mix nano silicon powder, carbon source material and conductive additive in a certain proportion and perform ball milling; Step 2, mixing the ball-milled mixture with an interface stabilizer and ball-milling again; Step 3: Drying the mixed materials; Step 4, carbonizing the dried mixture; Step 5: Mix the carbonized material with the alloying material to perform alloying treatment; Step 6: Mixing the treated material with a binder and a solvent to prepare a slurry; Step 7: coating the slurry on the current collector to form a negative electrode material coating; Step 8: The coated negative electrode material is subjected to secondary drying and tablet pressing to obtain a silicon-carbon negative electrode material.

2. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The addition ratio of the nano silicon powder, the carbon source material and the conductive additive in the step 1 is 5-7:2-3:5-10.

3. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The ball milling time in the step 1 is 10 to 20 hours.

4. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The interface stabilizer in step 2 is one of lithium fluoride and silicon dioxide, and the addition ratio is 1% to 5%.

5. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The drying temperature in step 3 is 80° C. to 120° C., and the drying time is 8 to 12 hours.

6. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The carbonization treatment temperature in step 4 is 600° C. to 900° C., and the treatment time is 2 to 4 hours.

7. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The alloying material in step five is one of tin, indium or gallium, and the addition ratio is 5-15%. The alloying treatment temperature is 300° C. to 500° C., and the treatment time is 1 to 3 hours.

8. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The binder in step six is ​​one of carboxymethyl cellulose, polyacrylic acid or conductive polymer.

9. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The secondary drying temperature of the coated negative electrode material in step eight is 80° C. to 120° C., and the drying time is 8 to 12 hours.

10. The method for preparing a silicon-carbon negative electrode material according to claim 1, characterized in that: The ball milling step involves processing using a high energy ball mill to ensure that the materials are thoroughly mixed and the particle size is reduced.

Citation Information

Patent Citations

  • Preparation method of silicon carbon composite anode material

    CN104900843A

  • Method for preparing silicon-carbon composite material based on ball milling method in air atmosphere and application of silicon-carbon composite material

    CN111900347A

  • Negative electrode material and preparation method thereof, secondary battery and electric equipment

    CN115084481A

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN117954585A

  • Preparation method for silicon-carbon composite anode material

    WO2016201979A1